Free guy [videorecording (DVD)] - Reynolds, Ryan; Comer, Jodie, 1993-; Waititi, Taika (Twentieth Century Fox Home Entertainment, 2021)
A bank teller, who discovers he is actually a background player in an open-world video game, decides to become the hero of his own story, one he rewrites himself. Now in a world where there are no limits, he is determined to be the guy who saves his world his way, before it is too late.